1 - The ‘Failure of the State’ of Cameroon: Between Sociopolitical Critique and Critical Social Science - Yenshu Vubo, Emmanuel (Africa Development, 2021)
Some discourses on the state of Cameroon have for some time been replete with critiques that oscillate between the political, the popular and the scientific. All are interwoven to produce a consensual mix between science, common sense and ideological statements. For the most part forecasting disaster, these discourses derive their sources from the mission reports of Bretton Woods institutions, powerful NGOs, opposition parties and intellectuals. Taking the talk on corruption and the management of public affairs (emblematic issues with which the country has been tagged) as a case in point, the article argues that the confusion between social categories of perception and scientific postures obscures the debate on this country by way of borrowings, intrusions and interferences. An exercise in the sociology of knowledge, the study examines the place of social knowledge in intellectual stand points and explores the conditions of social scientific statements.